2017
DOI: 10.1590/1980-5373-mr-2016-0963
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Castor Bark Powder as a Corrosion Inhibitor for Carbon Steel in Acidic Media

Abstract: The inhibition effect of castor bark powder obtained from Ricinus communis on AISI 1020 carbon steel in acidic media (HCl 0.5 mol.L -1 ) has been studied by electrochemical impedance spectroscopy (EIS), polarization curves, scanning vibrating electrode technique (SVET) and weight loss measurements. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were employed as characterization techniques. The EIS and gravimetric results showed that the inhibitory efficiency increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 54 publications
(80 reference statements)
2
54
1
5
Order By: Relevance
“…This phenomenon could be attributed to the chemisorption involving the charge transfer from the aqueous castor beans extract molecules to the mild steel surface. This behavior is different from the one presented by Santos et al, 14 where they concluded that the interaction between the molecules of the castor bark powder and the metal surface was physical due the ΔG°a ds calculation, which is in our point of view inappropriate.…”
Section: Temperature Effectcontrasting
confidence: 99%
See 3 more Smart Citations
“…This phenomenon could be attributed to the chemisorption involving the charge transfer from the aqueous castor beans extract molecules to the mild steel surface. This behavior is different from the one presented by Santos et al, 14 where they concluded that the interaction between the molecules of the castor bark powder and the metal surface was physical due the ΔG°a ds calculation, which is in our point of view inappropriate.…”
Section: Temperature Effectcontrasting
confidence: 99%
“…About the ΔG°a ds calculation performed by Santos et al, 14 in our previous works, 1,2,[10][11][12] we have shown that the determination of thermodynamic parameters such as ΔG°a ds was not possible, even when placing the water concentration in mg L −1 , due the unknown chemical nature of the adsorbed molecules.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…A erva mate (I. paraguariensis) é uma espécie vegetal nativa das regiões subtropicais e temperadas da América do Sul, o extrato desta erva e de outras folhas pode ser utilizado como inibidor de corrosão para aço inoxidável em soluções ácidas (Santos et al, 2017).…”
Section: Introductionunclassified